The effect of childcare on parental earnings trajectories - Matthias Krapf; Anja Roth; Michaela Slotwinski (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We study the effect of childcare availability on child penalties. Using Swiss administrative data, we exploit the staggered opening od childcare facilities across municipalities in the canton of Bern. We find that the presence of childcare facilities in the year of birth of the first child reduces the child penalty. The availability of childcare increases maternal earnings and decreases the compensating increase in fathers' earnings in households with below median earnings, but not in households with above median earnings. Although childcare affects relative earnings contributions within the household, there is no effect on total household earnings.
Keywords: D1; J00; J13; J16; H31; 330; child penalty; childcare; parental employment; gender wage gap